Gas exchange and chlorophyll fluorescence in spearmint (Mentha spicata L.) leaves influenced by mineral nutrition - Cano-Gallego, Lucas Esteban; Minchalá-Buestan, Nube; Loaiza-Ruíz, Ruby Alejandra; Cartagena-Valenzuela, José Régulo; Córdoba-Gaona, Oscar de Jesús (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The production of export-quality spearmint is limited in Colombia because of low production volumes, poor compliance with good agricultural practices, nutrient availability, and fertilization management. This study aimed to identify how NPK fertilization influences photosynthesis and photochemistry in Mentha plants during vegetative growth in a mesh house. Increasing doses of chemical fertilization were evaluated with a 10-30-10 (N-P-K) formula at 0, 60, 90, 120, and 180 kg ha-1. The evaluated variables were net photosynthesis (A), transpiration (E), stomatal conductance (gs), leaf temperature (Tleaf), quantum yield (Qy), Non-photochemical quenching (NPQ), photochemical quenching (qP), and dry matter (Dm). The highest A, Qy, E, and gs values were in the plants treated with high NPK doses; the NPQ and qP increased in the plants with low NPK doses. These findings elucidated the influence of NPK on photosynthesis and other physiological parameters in the growth and development of spearmint.